WORK-RELATED PROBLEMS AND PERFORMANCE LEVEL OF SENIOR HIGH SCHOOL TEACHERS : Received: 22nd September 2021; Revised: 16th February 2022, 20th February 2022, 05th March 2022; Accepted: 14th March 2022 - Reyes, Ricardo Carreon; Reyes, Jennifer P; Martinez, Ma Cecilia O (LIFE: International Journal of Health and Life-Sciences, 2022)
This descriptive correlational study determined the impact of work-related problems on the performance level of the 81 teachers in the Senior High School Department of a Local Government Funded University. Results showed: a combination of teachers, experienced to less experienced, mostly holding MA units, experienced work-compensation-related problems as their major problem. However, there were no significant relationship between the impact of their work-related problems experienced and their performance level in terms of classroom management skills, communication skills, instructional skills, knowledge of the subject matter, methods of evaluation, and teacher’s characteristics. In addition, there were no significant differences in the performance level in terms of classroom management, communication skills, instructional skills, knowledge of the subject matter, methods of evaluation, and teacher’s characteristics when grouped according to the length of work experience and highest educational attainment.